Pelatihan Pengoperasian Microsoft Word Sebagai Bentuk Implementasi Adaptasi Teknologi di SD Kusuma Putra - Nabila Sahda Brahmasta (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Information technology is a very important thing in various fields, especially in the field of education. One very important element is Microsoft Word because this element plays a very important role in creating effectiveness and efficiency in the work carried out. The aim of this research is to analyze the implementation of Microsoft Word operations training as a form of implementing technology adaptation at SD Kusuma Putra. The research method used is descriptive qualitative with interviews, observation and documentation as the data collection techniques used. The research results show that training in operating Microsoft Word consists of 3 stages, namely the preparation stage, the implementation stage and the analysis stage of the results of the training implementation. The training carried out by the researchers was carried out in 4 meetings. The results of implementing Microsoft Word training for grade 5 and 6 students at SD Kusuma Putra can have a positive impact on their ability to operate the Microsoft Word application. The training carried out makes students more enthusiastic in using the Microsoft Word application so that they can exercise their creativity when operating the Microsoft Word application.